Предмет: Алгебра,
автор: Neisvestniio
Упростите выражение с корнем
Помогите пожалуйста
Приложения:
Ответы
Автор ответа:
0
а)
√27*√50=
√(3*9)*√(5*10)=
√3*√9*√5*√10=
3*√3*√5*√2*√5=
3*5*√3*√2=
15√3√2
б)
√(1.2³)-√(0.3³)=
1.2^3/2-0.3^3/2=
1.2^1.5-0.3^1.5=
4^1.5*0.3^1.5-0.3^1.5=
8*0.3^1.5-0.3^1.5=
0.3^1.5(8-1)=
7*0.3^1.5
в)
(2+√3)(1-√3)+(2-√3)²=
2-2√3+√3-3+4-4√3+3=
2-3+4+3-2*√3+√3-4*√3=
6-5√3
Похожие вопросы
Предмет: Английский язык,
автор: SasaI3Dageztana
Предмет: Русский язык,
автор: тикамус
Предмет: Русский язык,
автор: малика67
Предмет: Английский язык,
автор: fiLthyMD
Предмет: Английский язык,
автор: seeeaaa